The Koran a very short introduction - Cook, Michael 1940- (Oxford Univ. Press, 2000)
The Koran has constituted a remarkably resilient core of identity and continuity for a religious tradition that is now in its fifteenth century. In this Very Short Introduction, Michael Cook provides a lucid and direct account of the significance of the Koran both in the modern world and in that of traditional Islam. He gives vivid accounts of its role in Muslim civilization, illustrates the diversity of interpretations championed by traditional and modern commentators, discusses the processes by which the book took shape, and compares it to other scriptures and classics of the historic cultures of Eurasia.
Keywords: Koran; Islam -- Customs and practices; Einführung